Analysis of Starbucks Marketing Strategy to Become a Luxury Brand - Naibaho, Nelly Artha; Manurung, Olivia Theresia; Jelita, Putri Dwi; Saragih, Lenti Susana (Indonesian Journal of Advanced Research, 2023)
The goal of a marketing strategy is of course to create added value for customers and achieve superiority over competitors in the market. Starbucks is one of the largest and most successful coffee companies in the world. In this case study, an analysis of Starbucks' marketing strategy is carried out so that it can become a luxury brand. Starbucks has and established a very strong marketing strategy and focuses on changing their brand image to be more exclusive and luxurious. This case study was completed through research using the internet searching method where information was obtained from various references, journals and articles. So it has been found that the marketing strategy by Starbucks includes; (1) always innovating products, (2) adding various menu variants, (3) offering merchandise, (4) outlets spread across various cities, (5) word of mouth marketing strategy, (6) building a loyalty program, (7) premium pricing strategy, (8) supporting social movements, (9) providing various attractive promotions, (10) using gimmicks. By implementing this excellent strategy, Starbucks was able to rank first in the most popular coffee in the coffee sector. Starbucks is also able to become a luxury brand because Starbucks itself offers high quality coffee beans from all over the world.